2017
DOI: 10.3389/fpls.2017.01241
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Calcium- and Hormone-Related Gene Expressions during Different Stages of Peanut Pod Development

Abstract: Peanut is one of the calciphilous plants. Calcium serves as a ubiquitous central hub in a large number of signaling pathways. In the field, free calcium ion (Ca2+)-deficient soil can result in unfilled pods. Four pod stages were analyzed to determine the relationship between Ca2+ excretion and pod development. Peanut shells showed Ca2+ excretion at all four stages; however, both the embryo of Stage 4 (S4) and the red skin of Stage 3 (S3) showed Ca2+ absorbance. These results showed that embryo and red skin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Sensibly, the groundnut is defined as geophytic geocarpy as they are supposed to be an aerial flowering by processing with burial of ovary below the ground covering with an organ of shell known as peg or gynophore (Barker, 2005). The transformation of peg to seed undergoes four types of biological regulation such as (i) gravity sensing or losing phototropism, (ii) auxin signalling, (iii) ethylene and gibberellin signalling, and (iv) embryonic development (Chen et al , 2016b; Kumar et al , 2019; Li et al , 2017). By defining the gravitropic‐related genes, they have been categorized in two such as positive gravitropism and negative gravitropism.…”
Section: Discussionmentioning
confidence: 99%
“…Sensibly, the groundnut is defined as geophytic geocarpy as they are supposed to be an aerial flowering by processing with burial of ovary below the ground covering with an organ of shell known as peg or gynophore (Barker, 2005). The transformation of peg to seed undergoes four types of biological regulation such as (i) gravity sensing or losing phototropism, (ii) auxin signalling, (iii) ethylene and gibberellin signalling, and (iv) embryonic development (Chen et al , 2016b; Kumar et al , 2019; Li et al , 2017). By defining the gravitropic‐related genes, they have been categorized in two such as positive gravitropism and negative gravitropism.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the processes like cell wall, transport, stress, transcription, signaling, UDP-D-xylose biosynthesis and UDP-sugars interconversion are related to cell wall synthesis and pod thickening during pod expansion/enlargement [ 26 ]. Other studies have reported the involvement of hormone-responsive genes in the pod development and maturation, like auxin-induced proteins, gibberellin beta-dioxygenases, ethylene-responsive transcription factor, cytokinin hydroxylase, cytokinin dehydrogenase, abscisic acid insensitive 5-like protein and abscisic acid hydroxylase [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole transcriptome shotgun sequencing, known as RNA-seq, is a widely used high-throughput approach that is known as second-generation sequencing technology. With the release of plant genome sequences including the potato [ 14 ], RNA-seq has becoming a powerful tool for transcriptome profiling, comparative gene expression analysis and gene identification [ 15 , 16 , 17 ]. Only several studies focused on using RNA-seq to identify genes involved in the potato response to late blight at the genome level.…”
Section: Introductionmentioning
confidence: 99%